LEGAL PROTECTION FOR CUSTOMER FUNDS AT VILLAGE CREDIT INSTITUTIONS (LPD) THROUGH A DEPOSIT GUARANTEE SCHEME BY THE EMPOWERMENT INSTITUTION FOR LPD - Ni Putu Ari Setyaningsih; I Ketut Satria Wiradharma Sumertajaya; Fanny Priscyllia (Warmadewa Press, 2022)
In the relevant Governor’s Regulations regarding LPD, it is not regulated regarding the value of guaranteed deposits for each customer at an LPD that is a participant in the deposit guarantee. The absence of legal regulations governing the value of deposits guaranteed through the LPD customer fund guarantee scheme has led to the need for a study of the extent of protection obtained by LPD customers for their deposit funds under this scheme. This research aims to examine deposit guarantee schemes for LPD customers and legal protection for customer funds at LPD through the loan fund scheme organised by LPLPD. This research is conducted using a normative juridical research method by conducting an analysis on primary legal materials and secondary legal materials related to the present research problems. Based on the analysis, it was found the LPD customer deposit guarantee scheme has not been able to provide legal protection to the customers. This is because in the deposit guarantee scheme, membership is discretionary so not all LPD customers in Bali get protection. The absence of regulation regarding the criteria to determine the amount of contribution and guarantee premium paid and the amount of customer deposits protected by the LPD customer deposit guarantee scheme has resulted in the absence of legal certainty regarding the amount of protected LPD customer funds.